Long-range attraction of an ultrarelativistic electron beam by a column of neutral plasma. (12th October 2016) - Adli, E; Lindstrøm, C A; Allen, J; Clarke, C I; Frederico, J; Gessner, S J; Green, S Z; Hogan, M J; Litos, M D; O'Shea, B; Yakimenko, V; An, W; et al.
Abstract: We report on the experimental observation of the attraction of a beam of ultrarelativistic electrons towards a column of neutral plasma. In experiments performed at the FACET test facility at SLAC we observe that an electron beam moving parallel to a neutral plasma column, at an initial distance of many plasma column radii, is attracted into the column. Once the beam enters the plasma it drives a plasma wake similar to that of an electron beam entering the plasma column head-on. A simple analytical model is developed in order to capture the essential physics of the attractive force. The attraction is further studied by 3D particle-in-cell numerical simulations. The results are an important step towards better understanding of particle beam–plasma interactions in general and plasma wakefield accelerator technology in particular.